Adaptive management of a machine-building enterprise under martial law - Pulina, Tеtiana; Aleksieienko, Oleksii; Aleksieienko, Viktoriia (Management and Entrepreneurship: Trends of Development, 2026)
The purpose of the article is to substantiate the theoretical and methodological foundations for the formation of an adaptive management system of a machine-building enterprise under martial law and to develop an integral indicator for assessing the level of its adaptability using the case of JSC “Motor Sich”.Methodology. The research is based on a systemic and structural approach to the analysis of adaptive management under conditions of military and economic instability. Methods of theoretical generalization, comparative analysis, formalization, and integral assessment were applied. The study identifies key external transformations affecting industrial enterprises, including market, financial, logistical, institutional, personnel, security, and technological risks. An integral adaptability index is constructed as a weighted sum of normalized values of seven functional indicators reflecting strategic flexibility, financial sustainability, risk management efficiency, organizational mobility, personnel adaptability, digital maturity, and production flexibility.Findings. It is substantiated that martial law significantly reshapes the external environment of machine-building enterprises, increasing uncertainty and systemic vulnerability. Adaptability acquires a multidimensional and integrated character, combining mechanisms of strategic response, financial stabilization, risk control, organizational restructuring, and digital transformation. The proposed methodology enables quantitative measurement of enterprise adaptability and provides a structured interpretation scale for evaluating its level.Originality. The scientific novelty lies in the development of a comprehensive model for measuring enterprise adaptability under martial law, integrating strategic, financial, organizational, digital, and production dimensions into a single integral index with justified weighting coefficients.Practical implications. The proposed assessment tool can be applied for strategic control and monitoring of managerial effectiveness at machine-building enterprises, particularly in the case of JSC “Motor Sich”. The model contributes to strengthening organizational resilience and creating a foundation for post-war recovery and sustainable development.JEL Classification: L23, M21, D81, O32